Formy ochrony szaty roślinnej w gminie Szadek - Woziwoda, Beata (Biuletyn Szadkowski, 2008)
As a result of a high degree of natural environment transformation in the neighbourhood of Szadek the variety of forms of nature protection is rather limited in this area. There is a nature reserve ,,Jamno” with an area of 22.56 ha established in 1959 to protect the fir and oak forest at the northerly limit of the area where the fir-tree is found. In old manor and village parks there are some very old trees – the register of nature monuments within the communes lists 24 such trees. There also are some areas of plants with protected status – about 45 species of plants designated as rare or threatened with extinction. Preservation of the natural environment in the commune requires long-range action, including both legal regulation and promotion of ecological awareness.